Characteristics and Utility of Fluorescein Breakup Patterns among Dry Eyes in Clinic-Based Settings - Chika Shigeyasu; Masakazu Yamada; Norihiko Yokoi; Motoko Kawashima; Kazuhisa Suwaki; Miki Uchino; Yoshimune Hiratsuka; Kazuo Tsubota; on behalf of the DECS-J Study Group (Diagnostics, 2020)
(1) Background: To evaluate the characteristics of fluorescein breakup patterns (FBUPs) among patients with dry eye disease (DED) and efficacy of FBUPs as a diagnostic test for DED subgroups. (2) Methods: The study enrolled 449 patients with DED. FBUPs were categorized as follows: area break (AB), line break (LB), spot break (SB), dimple break (DB), and random break (RB). Schirmer value, fluorescein breakup time (FBUT), keratoconjunctival score, DED subgroups and subjective symptoms were examined. (3) Results: LB patients presented with short FBUT and high keratoconjunctival score. AB patients presented with short FBUT, high cornea and keratoconjunctival scores. SB patients were young with short FBUT. DB patients exhibited low keratoconjunctival score. RB patients were young, with long FBUT and low keratoconjunctival scores. Among DED subgroups, LB and AB constituted 74.7% of aqueous-deficiency dry eye (ADDE). SB and DB constituted 42.4% of short FBUT dry eye (short FBUT-DE). Post-test probabilities and positive likelihood ratios for ADDE were 58.7% and 1.63, respectively; those for short FBUT-DE were 46.3% and 2.02, respectively. Patients with SB and AB exhibited significantly severe subjective symptoms than other FBUPs. (4) Conclusions: FBUPs are associated with both objective findings and symptoms of DED and may be a clinical tool for identification of DED subgroups.